2017
DOI: 10.1038/s41598-017-12553-7
|View full text |Cite
|
Sign up to set email alerts
|

Aligned hierarchical Ag/ZnO nano-heterostructure arrays via electrohydrodynamic nanowire template for enhanced gas-sensing properties

Abstract: Gas sensing performance can be improved significantly by the increase in both the effective gas exposure area and the surface reactivitiy of ZnO nanorods. Here, we propose aligned hierarchical Ag/ZnO nano-heterostructure arrays (h-Ag/ZnO-NAs) via electrohydrodynamic nanowire template, together with a subsequent hydrothermal synthesis and photoreduction reaction. The h-Ag/ZnO-NAs scatter at top for higher specific surface areas with the air, simultaneously contact at root for the electrical conduction. Besides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…The addition of noble metals, such as platinum (Pt) [18], palladium (Pd) [19], gold (Au) [20], and silver (Ag) [21,22], to the metal oxide structure can increase sensitivity and the selectivity. Weber et al [19] has revealed that through spillover effect, Pd can easily enhance the response of ZnO NWs gas sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of noble metals, such as platinum (Pt) [18], palladium (Pd) [19], gold (Au) [20], and silver (Ag) [21,22], to the metal oxide structure can increase sensitivity and the selectivity. Weber et al [19] has revealed that through spillover effect, Pd can easily enhance the response of ZnO NWs gas sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The measured S values of Pd‐ZnO with the flow rate of 100 ppm were 1.62, 0.49, and −1.82 for H 2 , CO, and NO 2 , respectively. For the Ag‐decorated ZnO, the measured S values were 0.58, 0.19, and −0.85 for H 2 , CO, and NO 2 , respectively, explained via electron transport across the interfaces between the Ag and the ZnO . In case of SnO 2 NPs, the sensitivities toward the gases were lower than those of ZnO NPs‐based sensors, may be explained by the low surface‐to‐volume ratio of the SnO 2 NPs.…”
Section: Resultsmentioning
confidence: 95%
“…The analog signals obtained in the sensors were processed by the analog-to-digital converter (ADC) of the STM32L4 microcontroller unit (MCU) to be transmitted to the main server for pattern recognition. [51] In case of SnO 2 NPs, the sensitivities toward the gases were lower than those of ZnO NPs-based sensors, may be explained by the low surface-to-volume ratio of the SnO 2 NPs. As the frequency increased to 3 Hz, the charged voltage increased to 1.71 V, enough to supply continuous power to each sensor element of the array at the same time, although there was a small reduction in the voltage when the switch to sensors was turned on (Figure 8b).…”
Section: Resultsmentioning
confidence: 96%
“…This behavior indicates that the Schottky barrier has formed at the metal-semiconductor contact. It is reported that the work function of ZnO (ϕ=5.2 eV) is larger than that of silver (ϕ=4.26 eV) [39]. Thus, the observed Schottky contact can be attributed to the differences between ZnO and Ag work functions [40].…”
Section: Optical Properties Of Zno Nanostructuresmentioning
confidence: 96%